Modified photo-current response of an organic photodiode by using V2O5 in both hole and electron transport layers - Abdullah, Shahino Mah; Rafique, Saqib; Azmer, Mohamad Izzat; Jilani, Asim; Sajith, V.K.; Supangat, Azzuliani (Elsevier, 2018)
In this study, we demonstrate a novel approach to use vanadium pentaoxide (V2O5) as a single material that can simultaneously function as both electron blocking and transport layers (EBLs and ETLs) in an organic photo-detector (OPD). Composite of V2O5 and PEDOT:PSS was introduced as hole transport layer (HTL) whereas, single V2O5 film was utilised as an ETL. The resultant device had the ITO/PEDOT:PSS+V2O5/PCDTBT:PC71BM/ V2O5/Al architecture and exhibited a new range of photo-current as well as showed an enhanced photo-response. For comparison, we also fabricated devices with ITO/PCDTBT:PC71BM/Al, ITO/PEDOT:PSS/PCDTBT:PC71BM/Al and ITO/PEDOT:PSS+V2O5/PCDTBT:PC71BM/Al architectures. The device with ITO/PCDTBT:PC71BM/Al architecture showed a photo-response in the range of ∼2.3 (OFF) to ∼6.7 mA/cm2 (ON) which increased to almost double after the inclusion of PEDOT:PSS as an HTL and reached to ∼2.3 and ∼12.6 mA/cm2 in OFF and ON states, respectively. In the third variant of devices with the addition of V2O5 in PEDOT:PSS to form a composite HTL, the photo-response narrowed down to ∼5.4 (OFF) and ∼12.6 mA/cm2 (ON). Lastly, the new approach with the addition of an ultrathin V2O5 layer as an ETL along with composite HTL demonstrated a new range of photo-current with enhanced photo-response in the range of 13.2 mA/cm2 (OFF) and ∼20.7 mA/cm2 (ON). The findings of the current work suggest that addition of V2O5 based ETL has tuned both photo-current and response range of the OPDs. In addition, inclusion of V2O5 into the PEDOT:PSS could effectively block the electrons due to its large band-gap.